Vectors of Domestic Policy of the General A.I. Denikin - A. V. Ishin (Проблемы постсоветского пространства, 2017)
In the article the basic vectors of reforms of administrations of the general Denikin, directed on strengthening of state machine and overcoming of the crisis phenomena are examined. Unknown sources are used before.